Radiomics Signature of Abdominal Aortic Aneurysm Neck: A Cross-Sectional Study - Maria Vieira Santos Silva (2022)
Objective: The aim of this study was to assess the feasibility of using a radiomic approach to study the proximal sealing zone of Abdominal Aortic Aneurysms (AAA) and to identify radiologic features of the neck that can predict inadequate endoprosthesis proximal sealing in patients undergoing Endovascular Aneurysm Repair (EVAR) surgery. Methods: This was an observational, retrospective, cross-sectional single-center pilot study. Patients were included from a retrospective database of consecutively admitted patients with AAA and submitted to EVAR in a tertiary university center, between 2009 and 2019. Patients with inadequate seal in their first postoperative Computed Tomography (CT) scan were identified and compared with a random sample of patients that had adequate seal. Segmentation of the preoperative neck of the AAA was performed using the 3DSlicer software. The PyRadiomics extension was then used to extract a total of 107 radiomic features from each segmentation. Partial least squares-discriminant analysis (PLS-DA) was used to identify the features that correlate the most with the sealing status after surgery. Results: A total of 40 patients were included in this study (17 with inadequate [<1cm] and 23 with adequate [≥1cm] sealing zones). Mean age was 73±7 (range 58 - 85 years) and 5% were women. Baseline characteristics were similar between the two groups. In experienced users, the whole process of segmentation and radiomic data extraction takes 5 minutes per patient. Thirty radiomic features were associated with neck sealing status including 2 first-order features, 11 features related to shape, and 17 related to texture in the PLS-DA. A model including these features was able to explain 14% of the variability between the groups. Conclusions: In this pilot study, radiomic signature based on non-contrast CT images explains part of the variability between patients that have adequate versus inadequate sealing after EVAR. This method might help with clinical decision about the adequacy of EVAR versus other treatment modalities. However, further research is needed with a larger sample size.